Phytochemical screening and antimicrobial activity of root and stem extracts of wild Eurycoma longifolia Jack (Tongkat Ali) - Khanam, Z.; Wen, C.S.; Bhat, I.U.H. (Journal of King Saud University, 2015)
Eurycoma longifolia Jack is a well-known traditional plant of Malaysia. It is popularly recognised as ‘Tongkat Ali’. The present study deals with the preliminary phytochemical screening and determination of antimicrobial activity of methanol, acetone, ethyl acetate, chloroform and petroleum ether extracts of the stem and root of E. longifolia. The extracts were tested against two gram positive bacteria, three gram negative bacteria and one fungus by the disc diffusion method at various concentrations (12.5–200 μg/μl). The results revealed the presence of phenolic compounds, flavonoids, terpenoids, alkaloids, protein and cardiac glycosides in the extracts. Stem extracts were found to be a rich source of phytochemicals as compared to the root extracts. All the extracts exhibited dose dependent antimicrobial activity, however, highest antibacterial activity was observed against gram positive bacteria by both stem and root extracts. Nevertheless, stem extracts were more potent than root extracts against Bacillus cereus and Staphylococcus aureus. Merely, ethyl acetate extract of the stem showed moderate activity against gram negative bacteria, Pseudomonas aeruginosa and high activity against fungus, Aspergillus niger. The preliminary studies on E. longifolia extracts exhibited their antimicrobial potential which could be exploited further as future antimicrobials for pharmaceutical treatment, natural therapies, food preservation and cosmetic applications.